Ceria/cobalt borate hybrids as efficient electrocatalysts for water oxidation under neutral conditions. Issue 9 (20th August 2019) - Zhou, Xuemei; Guo, Sijia; Cai, Qiran; Huang, Shaoming
Abstract : Oxygen evolution reaction (OER) catalysts are of importance for electrochemical water splitting and fuel generation. Abstract : Oxygen evolution reaction (OER) catalysts are of importance for electrochemical water splitting and fuel generation. Despite enormous efforts, the design and development of OER catalysts with high catalytic activities under neutral conditions are highly desired but still remain a great challenge. Herein, we report a room temperature chemical route to prepare x ceria/cobalt borate ( x CeO2 /Co–Bi) hybrids as efficient OER catalysts by tuning the molar ratio of Ce/Co ( x represents the amount of CeO2 ). The optimised catalyst (20CeO2 /Co–Bi hybrid) was found to exhibit remarkable OER catalytic activity with an overpotential of 453 mV at a current density of 10 mA cm −2, Tafel slope of 120 mV dec −1 and long-term stability in neutral medium due to its good conductivity, mass transportation and strong synergetic coupling effects, showing the potential of Co-based electrochemical materials for practical application in energy storage devices.